Analisis Al-Muwazanah (Paralelisme) dalam Surah Al-Ghasiyah Ayat 15-16 : Studi Analisis Ilmu Badi` - Habibah Khairani; Regina Valda Garzita; Siti Nurfadhillah; Harun Al Rasyid (Jurnal Budi Pekerti Agama Islam, 2025)
This article examines the concept of Al-Muwazanah in the science of balaghah and examples of the application of parallelism in classical Arabic language. Al-Muwazanah is a part of muhassinat al-lafdziyah that focuses on balance and symmetry in sentence structure or the repetition of patterns in two or more parts of a text. Al-Muwazanah is divided into two main types: parallelism in form (structural) and parallelism in meaning (thematic). This research employs a qualitative approach using the method of library study. Based on the analysis, numerous examples of Al-Muwazanah can be found in classical texts, demonstrating the beauty and balance in message delivery.